(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2017)
This paper identifies the nature of errors in the Percentage Syllable Articulation (PSA) test for Bangla, as a continuation and extension of a study conducted and published by the authors to determine the effects of Reverberation Time (RT) on Bangla. Errors due to RT 2.0 s are enumerated to derive Percent Error (PE) at initial, medial and final positions of phonemes in syllables, for both vowels and consonants. It is found that consonants are more vulnerable to errors than vowels, as their mean PEs are 37.8% and 27.6% respectively. Relative positions of phonemes in syllables have significant effect on PE. For vowels, mean PE increases from 12.1% to 56.7% for their medial and medial plus final positions respectively. For consonants, mean PE rises from 17.1% to 67.8% for their initial and final positions. Variations in PE within same groups of vowels and consonants, exemplify unique inherent characteristics of each phoneme. Bangladesh J. Sci. Ind. Res. 52(1), 21-30, 2017